1999
DOI: 10.1021/ol990739h
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Condensation of Pyrrole and Pentafluorobenzaldehyde:  A Novel Synthetic Pathway to Corrole and Oligopyrromethenes

Abstract: The solvent-free condensation of pyrrole and pentafluorobenzaldehyde (and to a lesser extent other electron-poor aldehydes as well) leads to a variety of products, of which three have been isolated and fully characterized. The two main products (11% each) are an open-chain pentapyrrole and corrole, a tetrapyrrolic macrocycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
195
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 280 publications
(210 citation statements)
references
References 15 publications
12
195
0
3
Order By: Relevance
“…Corroles have received a great deal of attention in recent years (10)(11)(12)(13), owing to dramatic advances in methods for their preparation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Of interest here is a gallium(III) complex, 1 [Ga(tpfc)] (32)(33)(34)(35), where tpfc represents the trianion of 5,10,15-tris(pentafluorophenyl)corrole [H 3 (tpfc)].…”
mentioning
confidence: 99%
“…Corroles have received a great deal of attention in recent years (10)(11)(12)(13), owing to dramatic advances in methods for their preparation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Of interest here is a gallium(III) complex, 1 [Ga(tpfc)] (32)(33)(34)(35), where tpfc represents the trianion of 5,10,15-tris(pentafluorophenyl)corrole [H 3 (tpfc)].…”
mentioning
confidence: 99%
“…[83,84] As early as 1996, Rose et al [85] reported the isolation of meso-tris(4-tert-butyl-2,6-dinitrophenyl)corrole as a minor by-product of a classical porphyrin synthesis, but the significance of this finding went almost unnoticed. The situation changed in 1999 with reports by Gross et al [86,87] and Paolesse et al [88,89] of one-pot corrole syntheses-initially still serendipitous-involving pyrrole-aldehyde condensations.…”
Section: One-pot Corrole Synthesesmentioning
confidence: 99%
“…[89] In contrast, the research group of Gross reported a fast, [86,87] essentially solvent-free, catalyst-free condensation of pyrrole with aldehydes in an open vessel in the presence of basic alumina as a solid support, followed by oxidation with DDQ in CH 2 Cl 2 to yield the correponding corroles. Gross and co-workers reported solvent-free syntheses of meso-tris(pentafluorophenyl)corrole ((TPFC)H 3 ), meso-tris(2,6-dichlorophenyl)corrole, and meso-tris(heptafluoropropyl)corrole [90] (Scheme 13), mentioning that their procedure worked best for relatively electron-deficient aldehydes.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent study was hampered by synthetic inaccessibility of corroles until 1999, when two new routes to the preparation of free base corrole were published by Paolesse 11 and Gross. 12,13 Over the next decade, a wealth of synthetic methodologies and variants were developed for synthesis of corroles, 14 with mesosubstituents, [15][16][17][18][19][20][21] various beta-substituents, [22][23][24][25][26] and eventually including both charged 27,28 and chiral 29 free-base corroles. The development of these organic syntheses is beyond the scope of this review, but the range of properties imparted by these synthetic options has greatly broadened the scope of applications of corroles.…”
Section: Introductionmentioning
confidence: 99%